Highly connected framework materials from flexible tetra-isophthalate ligands. Issue 18 (12th April 2022) - Chahine, Ali Y.; Chaffee, Alan L.; Knowles, Gregory P.; Turner, David R.; Batten, Stuart R.
Abstract : High connectivity octacarboxylate ligands containing non-coordinating diamine cores lead to a wide variety of new MOFs, many containing cage-like pores. Abstract : The design of metal–organic frameworks (MOFs) with high connectivity ligands is a potentially important approach towards enhanced stability materials and presents a powerful incentive in the self-assembly process towards high dimensionality networks, yet the MOF literature is dominated by di- and tri-carboxylate ligands. Herein, we report a new class of tetra-isophthalate "hyper-carboxylate" ligands containing flexible, linear diamine cores (H8 L1, containing 1, 2-diaminoethane; H8 L2, 1, 3-diaminopropane; H8 L3, 1, 4-diaminobutane; H8 L4, trans -1, 4-diaminocyclohexane). A series of MOFs based around copper(ii ) paddlewheel SBUs and these ligands has been found to regularly display cage-type cavities, not uncommon in isophthalate systems, that increase in size with longer diamine cores. However, with great flexibility comes great unpredictability, and a number of concomitant products were obtained in several instances. Notably the ligands, whilst all notionally able to connect to eight or more metal ions, are able to adopt a variety of coordination modes (coordinated to 8, 10, 12, or 14 metal ions) and topological connectivities (4-, 6-, and 8-connecting) as a consequence of their variable protonation states, in many instances leaving carboxylic acids directed into the framework channels. A variety of networks with other transition metals and node topologies further emphasise the unpredictability that can arise from having eight carboxylate groups in a single ligand including, somewhat surprisingly, two-dimensional coordination polymers. However, it is clear that despite the large variety of possible coordination modes leading to synthetic challenges in obtaining pure products, the use of highly decorated ligands is a strategy that generally trends towards three-dimensional networks of high connectivity.